The Mechanically Extraction Process of Gambier (Uncaria gambier Roxb.) from Limapuluh Kota, West Sumatera and Its Antioxidant activity - Galuh Widiyarti; Andini Sundowo; Euis Filailla; Joddy Arya Laksmono (The Journal of Pure and Applied Chemistry Research, 2020)
The extraction process from leaves and twigs of gambier (Uncaria gambier Roxb)plant was conducted mechanically by using traditional hydraulic press, conventional screw press, and modified twin-screw press. The leaves and twigs of gambier plant was obtained from traditional farmer in Limapuluh Kota, West Sumatera, Indonesia. The water, ash and catechin contents of the gambier extracts were analyzed based on SNI 01-3391-2000 using spectrophotometry and thermogravimetry method. Antioxidant activity analysis of the extracts was also performed by 1,1-diphenyl-2-picrylhidrazyl (DPPH) method and compared tovitamin C as a standard antioxidant. The analysis results showed that the extracts contain no ash. Meanwhile, the catechin and water contents of the extracts were approximately 50 and 13% thus the extracts were classified as quality gambier 2. Other than that, analysis result of catechin and epicatechin contents of the extracts using HPLC and compared to the reference materials showed that catechins contents of the extracts using traditional hydraulic press, conventionalscrew press, and modified twin-screw press give catechin content in about 94.296-95.030%. However, epicatechin was detected in a trace amount. The antioxidant activity of the extracts were 2.5 times stronger than reference. The IC50 value of 4.37-4.52 µg/mL and was categorized as active antioxidant.